Walking velocity and modified rivermead mobility index as discriminatory measures for functional ambulation classification of chronic stroke patients - Ji Young Lim; Seung Heon An; Dae-Sung Park (World Scientific Publishing, 2019)
Background: The cut-off values of walking velocity and classification of functional mobility both have a role in clinical settings for assessing the walking function of stroke patients and setting rehabilitation goals and treatment plans. Objective: The present study investigated whether the cut-off values of the modified Rivermead Mobility Index (mRMI) and walking velocity accurately differentiated the walking ability of stroke patients according to the modified Functional Ambulation Category (mFAC). Methods: Eighty two chronic stroke patients were included in the study. The comfortable/maximum walking velocities and mRMI were used to measure the mobility outcomes of these patients. To compare the walking velocities and mRMI scores for each mFAC point, one-way analysis of variance and the post-hoc test using Scheffe's method were performed. The patients were categorized according to gait ability into either mFAC=VII or mFAC≤VI group. The cut-off values for mRMI and walking velocities were calculated using a receiver-operating characteristic curve. The odds ratios of logistic regression analysis (Wald Forward) were analyzed to examine whether the cut-off values of walking velocity and mRMI can be utilized to differentiate functional walking levels. Results: Except for mFACs III and IV, maximum walking velocity differed between mFAC IV and mFAC V (p<0.01), between mFAC V and mFAC VI (p<0.001), and between mFAC VI and mFAC VII (p<0.05). The cut-off value of mRMI is >26.5 and the area under the curve is 0.87, respectively; the cut-off value for comfortable walking velocity is >0.77m/s and the area under the curve is 0.92, respectively; also, the cut-off value for maximum walking velocity is >0.92m/s and the area under the curve is 0.97, respectively. In the logistic regression analysis, the maximum walking velocity (>0.92m/s, OR=22.027) and mRMI (>26.5 scores, OR=10.283) are able to distinguish mFAC=VII from mFAC≤VI. Conclusion: The cut-off values of maximum walking velocity and mRMI are recommended as useful outcome measures for assessing ambulation levels in chronic stroke patients during rehabilitation.